2021
DOI: 10.1038/s41598-021-81913-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of deep and moderate neuromuscular blockade in microwave ablation of liver tumours: a randomized-controlled clinical trial

Abstract: Microwave ablation (MWA) is gaining popularity for the treatment of small primary hepatocellular carcinoma and metastatic lesions especially if patients are not candidates for surgical resection. Deep neuromuscular blockade (DMB) is perceived to improve surgical working conditions compared to moderate neuromuscular blockade (MMB) but no studies have examined the same benefits in MWA of liver tumours. This study aimed to compare the clinical outcomes of DMB and MMB in MWA of liver tumours in terms of liver excu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In recent years, a growing number of anesthesiologists have applied deep neuromuscular blockade technology in laparoscopic surgery to provide surgeons with better surgical space conditions so as to improve abdominal organ perfusion and alleviate postoperative pain for laparoscopic surgery [ 19 22 ]. The results of a meta-analysis by Bruintjes et al demonstrate that deep neuromuscular blockade improves surgical space conditions compared with moderate neuromuscular blockade in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing number of anesthesiologists have applied deep neuromuscular blockade technology in laparoscopic surgery to provide surgeons with better surgical space conditions so as to improve abdominal organ perfusion and alleviate postoperative pain for laparoscopic surgery [ 19 22 ]. The results of a meta-analysis by Bruintjes et al demonstrate that deep neuromuscular blockade improves surgical space conditions compared with moderate neuromuscular blockade in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing number of anesthesiologists have applied deep neuromuscular blockade technology in laparoscopic surgery to provide surgeons with better surgical space conditions so as to improve abdominal organ perfusion and alleviate postoperative pain for laparoscopic surgery. [19][20][21][22] The results of a meta-analysis by Bruintjes et al demonstrate that deep neuromuscular blockade improves surgical space conditions during laparoscopic surgery compared with moderate neuromuscular blockade. This study quanti ed surgical space conditions by measuring the distance from the sacral promontory to the umbilical skin.…”
Section: Discussionmentioning
confidence: 99%
“…The type of surgeries varied, including laparoscopic surgery [19, 23-27, 29-31, 33-38, 40, 42, 43, 45-47, 49-55], laparotomy [46], orthopedic surgery [16,17,28,48], thoracoscopic surgery [14,15], laryngeal surgery [12,13,41], urological surgery [39], and interventional radiography surgery [32,44]. Except for 8 studies comparing DNMB with non-MNMB [13, 25, 29, 46-48, 50, 51], the majority of studies compared DNMB with MNMB [12, 14-17, 19, 23, 24, 26-28, 30-45, 49, 52-55].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Adverse events. Twenty-one studies reported specific perioperative adverse events, which included but were not limited to vascular and organ injury [39,44,49], respiratory complications [14,23,34,35,39,40], cardiovascular complications, digestive complications [34], postoperative nausea and vomiting [17,30,31,33,38,40,41,44,48,50,52,53], incision complications [46], postoperative delirium [17], and shoulder pain [27,38,47]. The sample size was small, and the adverse events varied.…”
Section: Primary Outcomesmentioning
confidence: 99%